2008
DOI: 10.1248/jhs.54.356
|View full text |Cite
|
Sign up to set email alerts
|

.BETA.-Cryptoxanthin and Bone Metabolism: The Preventive Role in Osteoporosis

Abstract: Bone loss with aging induces osteoporosis. The most dramatic expression of the disease is represented by fractures of the proximal femur. Pharmacologic and nutritional factors may play a role in the prevention of bone loss with aging. β-Cryptoxanthin, a kind of carotenoid, is abundant in Satsuma mandarin orange (Citrus unshiu MARC.). Amoung various carotenoids including β-cryptoxanthin, lutein, lycopene, β-carotene, astaxanthin, and rutin, β-cryptoxanthin has been found to have a unique anabolic effect on bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…), preventing osteoporosis (Sugiura et al . ; Yamaguchi ) and the impact on human gene expression and cell differentiation (Handelman ). In addition, some researchers reported that carotenoids can be used as a marker to study the human dietary conditions (Hozawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…), preventing osteoporosis (Sugiura et al . ; Yamaguchi ) and the impact on human gene expression and cell differentiation (Handelman ). In addition, some researchers reported that carotenoids can be used as a marker to study the human dietary conditions (Hozawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…As with other carotenoids, b-Crp acts as an antioxidant and scavenges radicals (Miller, Sampson, Candeias, Bramley, & Rice-Evans, 1996) and stimulates the repair of oxidative damage to DNA (Lorenzo et al, 2009). Other studies have indicated that b-Crp reduces the risk of lung and colon cancers (Lian, Hu, Russell, & Wang, 2006;Miyazawa et al, 2007;Tanaka et al, 2000;Yuan, Stram, Arakawa, Lee, & Yu, 2003) and postmenopausal osteoporosis (Yamaguchi, 2008), suggesting that b-Crp has a wide range of beneficial functions in the body. However, effects of b-Crp on the immune system have not currently been investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Lutein and zeaxanthin have been related to a decreased risk of age‐related macular degeneration (AMD) and cataract 6. β ‐Cryptoxanthin has proven to have chemopreventive effects on cell migration of human stomach cells (BGC‐823) 7 and to also have a preventive role in osteoporosis in vitro 8. Capsanthin was shown to increase plasma HDL‐cholesterol levels on Wistar rats 9, a potent in vitro anti‐tumor activity in Epstein‐Barr virus activation assay in Raji cells, and in vivo anti‐tumor activity in mouse skin papillomas 10.…”
Section: Introductionmentioning
confidence: 99%